A Mixed‐Metal Porphyrinic Framework Promoting Gas‐Phase CO2 Photoreduction without Organic Sacrificial Agents. Issue 23 (24th August 2020) - Gao, Wen‐Yang; Ngo, Huong T.; Niu, Zheng; Zhang, Weijie; Pan, Yanxiong; Yang, Zhongyu; Bhethanabotla, Venkat R.; Joseph, Babu; Aguila, Briana; Ma, Shengqian
Abstract: A photoactive porphyrinic metal−organic framework (MOF) has been prepared by exchanging Ti into a Zr‐based MOF precursor. The resultant mixed‐metal Ti/Zr porphyrinic MOF demonstrates much‐improved efficiency for gas‐phase CO2 photoreduction into CH4 and CO under visible‐light irradiation using water vapor compared to the parent Zr‐MOF. Insightful studies have been conducted to probe the photocatalysis processes. This work provides the first example of gas‐phase CO2 photoreduction into methane without organic sacrificial agents on a MOF platform, thereby paving an avenue for developing MOF‐based photocatalysts for application in CO2 photoreduction and other types of photoreactions. Abstract : It's no sacrifice : A custom‐designed Ti/Zr porphyrinic metal−organic framework (MOF) demonstrates much‐improved efficiency for gas‐phase CO2 photoreduction into CH4 and CO under visible‐light irradiation using water vapor. This work provides the first example of gas‐phase CO2 photoreduction into methane without organic sacrificial agents on a MOF platform.